2012
DOI: 10.1002/chem.201202086
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Oxygenated Terphenyls and Other Oligomers: Sequential Arylation Reactions Through Phenol Oxidation–Rearomatization

Abstract: One by one: starting from simple phenols, a diverse series of oxygenated terphenyl compounds can be prepared in a concise and practical manner using sequential arylation reactions involving phenol oxidation/rearomatization and quinone monoacetal intermediates. Many of the terphenyl products can be used for preparing well-defined oligomers and, furthermore, contain valuable functional groups that can be transformed for further diversification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 56 publications
(16 reference statements)
1
18
0
1
Order By: Relevance
“…1‐Hydroxy‐4‐methoxy‐2‐(2,4,5‐trimethoxyphenyl)naphthalene (2ab): [17b] 1 H NMR (300 MHz, CDCl 3 ): δ = 8.39–8.32 (m, 1 H), 8.26–8.19 (m, 1 H), 7.59–7.47 (m, 2 H), 6.97 (s, 1 H), 6.73 (s, 1 H), 6.72 (s, 1 H), 6.70 (s, 1 H), 4.00 (s, 3 H), 3.97 (s, 3 H), 3.90 (s, 3 H), 3.86 (s, 3 H) ppm. 13 C NMR (75 MHz, CDCl 3 ): δ = 149.64, 149.59, 149.45, 144.56, 142.82, 126.53, 126.04, 125.88, 125.67, 122.75, 121.52, 119.53, 117.97, 115.37, 106.42, 98.96, 57.87, 56.61, 56.20, 55.82 ppm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1‐Hydroxy‐4‐methoxy‐2‐(2,4,5‐trimethoxyphenyl)naphthalene (2ab): [17b] 1 H NMR (300 MHz, CDCl 3 ): δ = 8.39–8.32 (m, 1 H), 8.26–8.19 (m, 1 H), 7.59–7.47 (m, 2 H), 6.97 (s, 1 H), 6.73 (s, 1 H), 6.72 (s, 1 H), 6.70 (s, 1 H), 4.00 (s, 3 H), 3.97 (s, 3 H), 3.90 (s, 3 H), 3.86 (s, 3 H) ppm. 13 C NMR (75 MHz, CDCl 3 ): δ = 149.64, 149.59, 149.45, 144.56, 142.82, 126.53, 126.04, 125.88, 125.67, 122.75, 121.52, 119.53, 117.97, 115.37, 106.42, 98.96, 57.87, 56.61, 56.20, 55.82 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…3‐( tert ‐Butyl)‐2‐hydroxy‐2′,4′,5,5′‐tetramethoxybiphenyl (4ab): [17d] R f = 0.33 (hexane/EtOAc, 3:1). 1 H NMR (300 MHz, CDCl 3 ): δ = 6.93 (d, J = 3.1 Hz, 1 H), 6.86 (s, 1 H), 6.67–6.64 (m, 2 H), 6.09 (s, 1 H), 3.95 (s, 3 H), 3.87 (s, 3 H), 3.83 (s, 3 H), 3.80 (s, 3 H), 1.45 (s, 9 H) ppm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dohi et al reported a sequential arylation method which involved oxidation followed by subsequent rearomatization of phenols to give oxygenated terphenyls along with a series of more elongated oligomers via quinone monoacetals as key intermediates (Scheme 63). [ 51 ] The reaction occurred in the presence of PIDA as an oxidant in methanol and montmorillonite (MT) clay as a solid acid promoter to form the aryl–aryl bond. The aryl quinone monoacetal obtained by the coupling of phenol with 1,3‐dimethoxy benzene was subjected to a variety of oxygenated aromatic nucleophiles and the corresponding oxygenated terphenyls were obtained in good to excellent yields.…”
Section: Hypervalent‐iodine and Molecular Iodine‐mediated Cross‐dementioning
confidence: 99%
“…[39] This method of dearomatization has been extensively utilized in the development of methodologies and organic synthesis (Scheme 7). [40]…”
Section: Preparation Of Para-quinols and 25cyclohexa-dienone Ketalsmentioning
confidence: 99%